2020
DOI: 10.1101/2020.03.05.979112
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differentiation reveals the plasticity of age-related change in murine muscle progenitors

Abstract: Skeletal muscle experiences a decline in lean mass and regenerative potential with age, in part due to intrinsic changes in progenitor cells. However, it remains unclear if age-related changes in progenitors persist across a differentiation trajectory or if new age-related changes manifest in differentiated cells. To investigate this possibility, we performed single cell RNA-seq on muscle mononuclear cells from young and aged mice and profiled muscle stem cells (MuSCs) and fibro/adipose progenitors (FAPs) afte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 110 publications
(175 reference statements)
1
23
0
Order By: Relevance
“…CellRank is a method to quantitatively analyze RNA velocity-induced vector fields in high dimensions. While other approaches have started to address this, they either ignore the stochastic nature of cellular fate decisions and velocity uncertainty 76,77 , or they focus on questions other than trajectory reconstruction 78 . The original velocyto 18 model proposed an idea to find initial and terminal states that was based on simulating a Markov process forwards or backwards in time, however, their implementation relied on a 2D t-SNE embedding, was computationally expensive because of the sampling, ignored uncertainty in velocity vectors and did not allow the separation into individual initial and terminal states.…”
Section: Discussionmentioning
confidence: 99%
“…CellRank is a method to quantitatively analyze RNA velocity-induced vector fields in high dimensions. While other approaches have started to address this, they either ignore the stochastic nature of cellular fate decisions and velocity uncertainty 76,77 , or they focus on questions other than trajectory reconstruction 78 . The original velocyto 18 model proposed an idea to find initial and terminal states that was based on simulating a Markov process forwards or backwards in time, however, their implementation relied on a 2D t-SNE embedding, was computationally expensive because of the sampling, ignored uncertainty in velocity vectors and did not allow the separation into individual initial and terminal states.…”
Section: Discussionmentioning
confidence: 99%
“…4B). It has previously been reported that aged myogenic cells do not differentiate into mature myocytes as effectively as young cells [51,23]. We found that transiently reprogrammed aged cells were more differentiated than aged control cells based on pseudotemporal distributions, expression of marker genes, and gene set analysis (Fig.…”
Section: Transient Multipotent Reprogramming Improves Myogenesis In Aged Cellsmentioning
confidence: 53%
“…We first wanted to determine if the transcriptional distance between young and aged control cells – the magnitude of aging – was decreased by transient reprogramming. We measured the magnitude of aging using the maximum mean discrepancy (MMD), a statistic from representation learning that measures the similarity of two populations and provides a test for statistical significance [22, 23]. Here, we computed the MMD across cell populations using autoencoder latent variables to capture changes across the entire transcriptome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations